Sclerosing polycystic adenosis: A rare tumor misdiagnosed as retention cyst on fine needle aspiration cytology. Issue 7 (22nd March 2017) - Shilpi,; Ahmad Ansari, Fuzail; Bahadur, Shalini; Katyal, Akshi; Narula, Aastha; Nargotra, Namrata; Singh, Sompal
Abstract : Sclerosing polycystic adenosis (SPA) is a rare benign neoplasm of the salivary gland which resembles the fibrocystic disease of the breast clinically as well as morphologically. This entity has varied morphological presentation on fine needle aspiration. Only a few case reports and occasional case series are found in the literature describing its cytology. Here we are presenting a case of SPA in the parotid gland in a 13‐year‐old male patient who presented with a slow growing infra‐auricular mass since one year without any other symptoms. Radiological investigation suggested a possibility of matted level II cervical lymph nodes. Fine needle aspiration of the same showed only crystalloids in a dirty background. Hence, a possibility of retention cyst was given and excision was advised. On histopathological examination, the mass was diagnosed as Sclerosing polycystic adenosis of the parotid gland. Since SPA is a rare entity with diverse morphological features, it is more likely to be misdiagnosed on cytology. Recognition of this benign entity is important since the differential diagnosis includes other more common benign and malignant salivary gland neoplasm particularly mucoepidermoid carcinoma and other tumors with cystic and oncocytic features. Repeat aspiration from multiple sites should be considered in cystic lesions of the salivary gland so that its varied cytological components can be yielded to help with the diagnosis. Diagn. Cytopathol. 2017;45:640–644. © 2017 Wiley Periodicals, Inc.